“O ensino da Dinâmica e o uso do jogo de tabuleiro Dinâmica da Física como estratégia didática” - Claudino, Fernando (2016)
Interpersonal relationships have an extremely important role in the formation of individuals for the construction of knowledge is through the interaction of society subjects. This knowledge is all the more relevant as more is inserted in the cultural context of the people who produce it. This study aimed at the development and implementation of an educational game for teaching dynamics for the first year of high school. The didactic experiment was conducted in a public school in the city of Maceió-AL. Through this study we sought to respond to the impact of the application of the card game Dynamic physics for teaching dynamics in the first year of high school classes was positive. The research is based on the interactionism partner Vygotsky's theory and the theory of meaningful learning of Ausubel. Its nature is qualitative and applied approach in the resolution of the problem teaching dynamics with card game as a teaching strategy. What could be observed was that the use of game physics classes enabled the development of social relations between teacher and students and between students with each other, and through the application of evaluation activities, it became clear a development in the cognitive abilities of these students in 95% of cases.